Neuroprotection after cardiac arrest with 2-iminobiotin: a single center phase IIa study on safety, tolerability, and pharmacokinetics - Admiraal, M. M.; Velseboer, D. C.; Tjabbes, H.; Vis, P.; Peeters-Scholte, C.; Horn, J. (Frontiers in Neurology, 2023)
Background Brain injury is a serious problem in patients who survive out-of-hospital cardiac arrest (OHCA). Neuroprotective drugs could reduce hypoxic–ischemic reperfusion injury. The aim of this study was to investigate the safety, tolerability, and pharmacokinetics (PK) of 2-iminobiotin (2-IB), a selective inhibitor of neuronal nitric oxide synthase. Methods Single-center, open-label dose-escalation study in adult OHCA patients, investigating three 2-IB dosing schedules (targeting an AUC0-24h of 600–1,200 ng*h/m in cohort A, of 2,100–3,300 ng*h/mL in cohort B, and 7,200–8,400 of ng*h/mL in cohort C). Safety was investigated by monitoring vital signs until 15 min after study drug administration and adverse events up to 30 days after admission. Blood sampling for PK analysis was performed. Brain biomarkers and patient outcomes were collected 30 days after OHCA. Results A total of 21 patients was included, eight in cohort A and B and five in cohort C. No changes in vital signs were observed, and no adverse events related to 2-IB were reported. A two-compartment PK model described data the best. Exposure in group A (dosed on bodyweight) was three times higher than targeted (median AUC0-24h 2,398 ng*h/mL). Renal function was an important covariate; therefore, in cohort B, dosing was performed on eGFR on admission. In cohort B and C, the targeted exposure was met (median AUC0-24h 2,917 and 7,323 ng*h/mL, respectively). Conclusion The administration of 2-IB to adults after OHCA is feasible and safe. PK can be well predicted with correction for renal function on admission. Efficacy studies with 2-IB after OHCA are needed.